Some insights on the optimal schemes of tall guyed masts - Belevičius, Rimantas; Jatulis, Donatas; Šešok, Dmitrij (Journal of Civil Engineering and Management, 2013)
The article presents the technique for simultaneous topology, shape and sizing optimisation of tall guyed masts under wind loadings and self-weight using simulated annealing. The objective function is the mass of the mast structure including guys, while the set of design parameters may consist of up to 10 parameters of different nature. The constraints are assessed according to Eurocodes and include the local and global stability constraints, limitations on the slenderness in mast elements, and strength constraints. The proposed optimisation technique covers three independent parts: the optimisation algorithm, meshing pre-processor that yields computational scheme of mast depending on the design parameters, and finite element program evaluating the objective function and constraints via penalisation technique. As an example the results of optimisation of a typical 60 m tall guyed telecommunication mast with different antenna areas are presented. On the basis of these results, the authors try ascertaining the approximate optimal diapasons of geometry and topology parameters such as the width of the shaft, distance of the guy foundation from the mast axis, heights of the guy attachment levels and so on. The authors hope, this will be helpful for constructors as an initial design of mast topology, shape and element sizing.